On the Role of Basal Autophagy in Adult Neural Stem Cells and Neurogenesis - Casares-Crespo, Lucía; Calatayud-Baselga, Isabel; García-Corzo, Laura; Mira, Helena (Frontiers in Cellular Neuroscience, 2018)
Adult neurogenesis persists in the adult mammalian brain due to the existence of neural stem cell (NSC) reservoirs in defined niches, where they give rise to new neurons throughout life. Recent research has begun to address the implication of constitutive (basal) autophagy in the regulation of neurogenesis in the mature brain. This review summarizes the current knowledge on the role of autophagy-related genes in modulating adult NSCs, progenitor cells and their differentiation into neurons. The general function of autophagy in neurogenesis in several areas of the embryonic forebrain is also revisited. During development, basal autophagy regulates Wnt and Notch signaling and is mainly required for adequate neuronal differentiation. The available data in the adult indicate that the autophagy-lysosomal pathway regulates adult NSC maintenance, the activation of quiescent NSCs, the survival of the newly born neurons and the timing of their maturation. Future research is warranted to validate the results of these pioneering studies, refine the molecular mechanisms underlying the regulation of NSCs and newborn neurons by autophagy throughout the life-span of mammals and provide significance to the autophagic process in adult neurogenesis-dependent behavioral tasks, in physiological and pathological conditions. These lines of research may have important consequences for our understanding of stem cell dysfunction and neurogenic decline during healthy aging and neurodegeneration.